Hyperkinetic Seizures with Ictal Fear as Localizing Ictal Signs in MRI-Negative Medial Frontal Lobe Epilepsy - Cloppenborg, Thomas; Albers, Kristina; Kalbhenn, Thilo; Woermann, Friedrich G.; Bien, Christian G.; Polster, Tilman (Neuropediatrics, 2020)
Purpose Hyperkinetic seizures are described as seizure onset in the frontal or temporal lobe. Additional localizing information is important for diagnostic workup and surgical therapy. We describe diagnostic workup and surgical outcomes in three patients with pharmacoresistant focal emotional seizures with hyperkinetic elements.Methods/Results High-resolution 3 Tesla (T) magnetic resonance imaging (MRI) did not reveal clear-cut lesions. Invasive video-electroencephalography (EEG) with depth electrodes along the cingulate sulcus (bilateral; patients 1 and 3), right; patient 2 provided congruent results for a circumscribed seizure onset zone within the medial frontal lobe (right: patients 1 and 2; left: patient 3). Topectomies were performed in all patients. Histopathology revealed a small focal cortical dysplasia in the three cases (focal cortical dysplasia [FCD] IIA: patient 1; FCD IIB: patients 2 and 3). All patients remained completely seizure-free since surgery (Engel 1A; follow-up: 9–28 months).Conclusion Ictal fear associated with hyperkinetic semiology points to a seizure-onset zone within the anteromedial frontal lobe (anterior cingulate gyrus). Ictal semiology is crucial for the placement of depth electrodes, especially in MRI-negative cases. These cases illustrate a clinical advantage to the new International League against Epilepsy (ILAE) seizure classification, emphasizing initial clinical symptoms.
Keywords: epilepsy surgery; ictal semiology; nonlesional; frontal lobe seizures